2005
DOI: 10.1179/174239505x56012
|View full text |Cite
|
Sign up to set email alerts
|

'What is expressed is not always what is felt': coping with stigma and the embodiment of perceived illegitimacy of multiple sclerosis

Abstract: MS sufferers apply a tactic of protective disclosure by which they seek to guard their sense of self. The strategy of preventive disclosure is employed to obtain assistance from others. Furthermore, the strategy of concealing MS is conducted purposefully to prevent the sufferer being deprived of social belonging, especially with regard to work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 0 publications
4
20
0
3
Order By: Relevance
“…) which suggests the concept of the liminal self may have relevance to other chronic conditions. In keeping with the findings from previous studies, the findings support uncertainty as an ongoing feature of the lived experience with the prevailing threat of relapse (Johnson , Grytten & Måseide ). However, the current study draws attention to the experience of the individual whose symptoms of MS may not be considered as particularly intrusive.…”
Section: Discussionsupporting
confidence: 88%
“…) which suggests the concept of the liminal self may have relevance to other chronic conditions. In keeping with the findings from previous studies, the findings support uncertainty as an ongoing feature of the lived experience with the prevailing threat of relapse (Johnson , Grytten & Måseide ). However, the current study draws attention to the experience of the individual whose symptoms of MS may not be considered as particularly intrusive.…”
Section: Discussionsupporting
confidence: 88%
“…The present study suggests that some participants have difficulty disclosing their MS diagnosis as they fear causing distress to loved ones and fear negative reactions from others. These results accord with research suggesting that people with MS demonstrated disability by using crutches, for example, and felt that this helped them to feel in control by signalling that something was wrong, whilst others disclosed their MS to new acquaintances in order to avoid being viewed as ‘drunk’[15]. People with MS disclose or conceal their MS diagnosis in order to counteract devaluing social interactions [15].…”
Section: Discussionsupporting
confidence: 81%
“…For example, over time, people might adapt to MS by surrounding themselves with supportive others, educating others about their illness, and strategically choosing to conceal or disclose their MS status. 13,[16][17][18] If so, as people gain experience coping with MS, they may be less likely to anticipate or experience being a target of stigma. [19][20][21][22] Consistent with this adjustment view, people with MS often describe developing a more positive, optimistic outlook over time.…”
Section: Surveymentioning
confidence: 99%